Оптимізація компонування сферичних об’єктів у багатогранній області - Романова, Т.Є.; Яськов, Г.М.; Чугай, А.М.; Стоян, Ю.Є. (Кібернетика та комп’ютерні технології, 2020)
Розглянуто задачу компонування сферичних об'єктів змінних радіусів із змінними пара-метрами розміщення у обмеженій багатогранній області із урахуванням обмежень на допустимі мінімальні відстані з метою максимізації сумарного об’єму розміщуваних об'єктів. The purpose of the article is presenting a mathematical model and developing a solution algorithm for ar-ranging spherical objects in a polyhedral region with the maximum packing factor. It allows obtaining a locally optimal solution in a reasonable time. Results. A new formulation of the problem of arranging spherical objects in a polyhedral domain is con-sidered, where both the placement parameters and the radii of the spherical objects are variable. A mathemati-cal model in the form of nonlinear programming problem is derived. A solution approach based on the decom-position algorithm and multistart strategy is developed. The numerical results combined with the graphical illustration are given.